F(g(x))= 3(6x+2)-5=18x+6-5=18x+1,
so correct answer is the last one
Answer:
Step-by-step explanation:
x^2 + 2x = 6x+45
x^2 -4x -45 =0
x^2 - 5x +9x -45 =0
x(x-5) +9 (x-5)=0
(x-5)(x+9)=0
x = 5, -9
x = 5; measure of exterior angle = 5^2+2(5) = 35
x=-9; measure of exterior angle = (-9)^2 + 2(-9) = 63
The Power of a Power Rule. In this case, you basically multiply the two exponents together, and simplify (x^4)^9 to equal x^36
9 to the 3rd power is 729
And 2 to the 5th power is 32. You multiple 9, 3 times. 9 times 9 times 9 and you multiply 2, five times. 2 times 2 times 2 times 2 times 2
Answer:
x = 2
y = -3
z = 4
( 2 , -3, 4 )
Step-by-step explanation:
x + y + z = 3 ---- i
x – y =5 ---- ii
y - z = -7 ---- iii
ii + iii
x - z = -2 ---- iv
i + ii
2x + z = 8 --- v
iv + v
3x = 6
x = 2
x=2 substitute for v
z = 4
x =2 substitute for ii
y = -3